An Interview Survey on Species Protection Aspects Among Residents of Three Communities in the Mt. Talinis Area, Negros Oriental - Schales, Christian K. (Silliman Journal, 2022)
Residents living close to the residuals of virgin rain forest in about sightings, nesting places, and potential hunting and trapping of the two bird species Aceros waldeni and Penelopides panini. The results show that Penelopides panini. The results show that Aceros waldeni is very rare that Penelopides panini occurs more frequently. Hunting and trapping of Aceros waldeni and Penelopides panini possible still takes place. The paper also includes data about various other, partly endangered, species seen and hunted in the research area. All respondents claimed that they have a postive attitude towards protecting Aceros waldeni and Penelopides panini.